Family History of Head and Neck Cancers - Li, Xinjun; Koskinen, Anni I; Hemminki, Otto; Försti, Asta; Sundquist, Jan; Sundquist, Kristina; Hemminki, Kari (Cancers, 2021)
BACKGROUND: Head and neck cancers (HNCs) encompass a heterogeneous group of cancers between the mouth and larynx. Familial clustering in HNCs has been described, but how it influences individual sites and to which extent known risk factors, such as human papilloma virus (HPV) infection, may contribute is not well established. PATIENTS/METHODS: We employed standardized incidence ratios (SIRs) to estimate familial risks for HNC with same (concordant) and different (discordant) cancers among first-degree relatives using data from the Swedish Cancer Registry from 1958 to 2018. RESULTS: Incidence for male and female oropharyngeal cancer increased close to four-fold in the past 39 years. Familial HNC was found in 3.4% of the study population, with an overall familial SIR of 1.78. Patients with concordant nasopharyngeal cancer showed a high risk of 23.97, followed by hypopharyngeal cancer (5.43). The husbands of wives with cervical cancer had an increased risk of oropharyngeal cancer. DISCUSSION/CONCLUSION: Nasopharyngeal cancers lacked associations with lifestyle or HPV associated cancers, suggesting a role for germline genetics, which was also true for the high-risk families of three HNC patients. In the Swedish population with low smoking levels, HPV is becoming a dominant risk factor, emphasizing the need for sexual hygiene and HPV vaccination.
Keywords: genetic factors; oral cancer; human papilloma virus; smoking; pharyngeal cancer